2015
DOI: 10.5152/tftrd.2015.70188
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Features of Hospitalized Multiple Sclerosis Patients Undergoing a Rehabilitation Program at our Clinic

Abstract: Objective: The aim of this study was to investigate the sociodemographic and clinical characteristics as well as rehabilitation methods of patients with multiple sclerosis (MS) undergoing an inpatient rehabilitation program. Material and Methods: A retrospective analysis of 104 patients with MS from 2007 to 2012 undergoing a rehabilitation program in a special rehabilitation unit was performed. Sociodemographic data were recorded. Disease-related characteristics such as disease duration, initial symptoms, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Since MS generally affects young adults, the work and social and family life of the patients are negatively affected. 34 Fatigue, one of its most common symptoms, also contributes to inadequate employment and early retirement. Studies have also reported that most MS patients do not work.…”
Section: Discussionmentioning
confidence: 99%
“…Since MS generally affects young adults, the work and social and family life of the patients are negatively affected. 34 Fatigue, one of its most common symptoms, also contributes to inadequate employment and early retirement. Studies have also reported that most MS patients do not work.…”
Section: Discussionmentioning
confidence: 99%